Analysis of the Level of Public Trust in Zakat Management by Laziznu Metro City Through Partnership with BMT Artha Buana Metro - Putri Lestari Ramadhani; Haris Santoso (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the level of public trust in zakat management by LAZISNU Metro City and to determine the role of the partnership between LAZISNU Metro City and BMT Artha Buana Metro in improving the effectiveness of zakat management. This research uses a qualitative approach with a descriptive method. Data were obtained through interviews, observations, and documentation with informants consisting of the Head of LAZISNU Metro City, the Manager of BMT Artha Buana Metro, and one of the muzakki. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the level of public trust in zakat management by LAZISNU Metro City is still not fully optimal, as some people still prefer to distribute their zakat directly to mustahik. However, from the institutional perspective, the level of public trust shows an increase, which is indicated by the growing number of muzakki and community participation in LAZISNU social programs. The partnership between LAZISNU Metro City and BMT Artha Buana Metro is implemented in the form of cooperation in the collection and distribution of zakat funds in a formal and administrative manner. Factors influencing public trust include trust in the institution, a well-planned organizational work system, centralized management of zakat funds, and the mechanism of zakat distribution carried out through a survey process of prospective mustahik. Based on these findings, it is recommended that LAZISNU Metro City continue to improve transparency and accountability in zakat management, strengthen public socialization regarding the importance of distributing zakat through official institutions, and optimize cooperation with Islamic financial institutions such as BMT to enhance the effectiveness of zakat collection and distribution.